1971
DOI: 10.1111/j.1600-0609.1971.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Studies on the Decay of Lymphocytes in the Blood of the Mouse

Abstract: The number of decaying lymphocytes in the peripheral blood of the mouse was determined by means of the dye exclusion test. Under normal conditions the lymphocyte decay was very constant (1.1%). Treatment with pertussis vaccine, anti‐lymphocyte serum, and hydrocortisone either alone or in combination greatly influenced the number of decaying blood lymphocytes. Treatment with heparin markedly increased the number of circulating non‐viable lymphocytes, probably due to inhibition of the reticuloendothelial macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Furthermore, labelling percentages of unseparated and separated small lymphocytes indicated that no selective loss of labelled or unlabelled cells occurred during the process of separation. About 1.6 % of blood lymphocytes were found to decaya value very close to that obtained in previous work (Claesson & Olsson 1971).…”
Section: Discussion and Calculationssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, labelling percentages of unseparated and separated small lymphocytes indicated that no selective loss of labelled or unlabelled cells occurred during the process of separation. About 1.6 % of blood lymphocytes were found to decaya value very close to that obtained in previous work (Claesson & Olsson 1971).…”
Section: Discussion and Calculationssupporting
confidence: 89%
“…The lymphocytes in peripheral blood consist of subpopulations which differ with respect to 1967)* Dye studies have shown that about 1 % of murim blood lymphocytes are dying (Claesson & Olsson 1971). These life spans (Everett ~ -. dying lymphocytes are probably derived blood was mixed with equal amounts Of a 1.8 % citrat solution and layered on 0.3 ml Lymphoprep (Nygaard L Co.; Oslo) and centrifuged at 300 G for 15 min.…”
mentioning
confidence: 99%